Fushenmu treatment ameliorates RyR2 with related metabolites in a zebrafish model of barium chloride induced arrhythmia - Yan-Ting Zhao; Yan-Ru Liu; Ya-Feng Yan; Zhi-Shu Tang; Jin-Ao Duan; Hui Yang; Zhong-Xing Song; Xue-Lian You; Ming-Geng Wang (BMC, 2023)
Abstract Background Fushenmu (Pini Radix in Poria, FSM) is a folk parasitic herb that has been mainly used for palpitation and amnesiain in traditional Chinese medicine (TCM). Recently, as an individual herb or a component of formulations, Fushenmu exhibits therapeutic potential for the treatment of cardiac arrhythmias. Yet, how specific targets or pathways of Fushenmu inhibit arrhythmia has not yet been reported. Methods Here, based on clinical functional genomics, metabolomics and molecular biologic technologies, a network construction strategy was adopted to identify FSM therapeutic targets and biomarkers that might explore its functions. Results In this study, it was found that FSM recovered arrhythmia-associated heart failure in barium chloride (BaCl2) induced arrhythmic zebrafish embryos, as was evidenced by the shortened cardiac sinus venosus-bulbus arteriosus (SV-BA) distance, smaller cardiovascular bleeding areas, and reduced cardiomyocyte apoptosis. Moreover, analysis via ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-QTOF-ESI-MS/MS) components identification and network pharmacology prediction showed that 11 main active components of FSM acted on 33 candidate therapeutic targets. Metabolomic analysis also suggested that FSM could rescue 242 abnormal metabolites from arrhythmic zebrafish embryos. Further analysis based on the combination of target prediction and metabolomic results illustrated that FSM down-regulated Ryanodine Receptor 2 (RyR2) expressions, inhibited adrenaline and 3',5'-Cyclic AMP (cAMP) levels in a dose-dependent manner, which was confirmed by metabolites quantification and quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) assay. Conclusion In summary, this study revealed that FSM mitigated BaCl2 induced cardiac damage caused by arrhythmia by suppressing RyR2 expressions, decreasing adrenaline and cAMP through the adrenergic signalling pathway.